The Efficacy and Safety of Radiofrequency Ablation for Bilateral Papillary Thyroid Microcarcinoma - Yan, Lin; Zhang, Mingbo; Song, Qing; Xiao, Jing; Zhang, Ying; Luo, Yukun (Frontiers in Endocrinology, 2021)
Objective: To investigate the long-term clinical results of radiofrequency ablation (RFA) for bilateral papillary thyroid microcarcinoma (PTMC). Materials and Methods: From October 2014 to February 2018, 47 patients(37 females, 10 males, mean age 43.39±9.26 years) with 100 bilateral PTMC(mean volume 75.22±73.87mm3) treated by RFA were included in this retrospective study. Bilateral PTMC was defined as at least one tumor located in the contralateral lobe. Patients were followed up at 1, 3, 6, 12 months and every 6-12 months thereafter. Volume, volume reduction ratio(VRR) and local tumor recurrence were evaluated during the follow-up period. Results: After a mean follow-up period of 47.77±11.54 months, the mean volume of bilateral PTMC decreased from 75.22±73.87mm3 to 0.09±0.44mm3. The mean VRR was 99.94±0.28% and the complete disappearance rate was 92.00%. During the follow-up, one patient(2.13%) developed lymph node metastasis and 2 patients(4.26%) had recurrent PTMC. All the recurrent lesions underwent additional RFA and two of them disappeared completely. No life-threatening or delayed complications occurred. Conclusions: With sufficient preoperative evaluation, RFA might be a promising alternative for bilateral PTMC patients who were unsuitable for surgery or refused surgery.